Probing cosmic inflation with the Spider experiment - Padilla, Ivan (2019)
Spider is a balloon-borne cosmic microwave polarimeter designed to operate for up to two weeks on a Long Duration Balloon platform. From above 99.5% of the atmosphere, Spider flew over Antarctica for 16 days observing the sky with over two thousand detectors housed inside a 1300 L liquid helium cryostat, distributed amongst 6 telescopes that span two frequency channels: 95 GHz and 150 GHz. By focusing its observing time over a 10% patch of the sky at high galactic latitude, Spider targets the degree-scale BB spectrum in search of the pattern that would have been imprinted by gravitational waves propagating in the early universe, a key prediction of inflation. In order to probe the physics of the very early universe the experiment needs to operate in the harsh environment of the upper atmosphere for multiple days. This work discusses at length the detailed thermal modeling and analysis leading up to the 2015 flight which ensured the correct thermal operation of every component while at 36 km of altitude. The flight is followed by a data analysis that will ultimately produce a constraint on the amplitude of the primordial gravitational wave background from bandpowers of the BB spectrum of the CMB. In order to measure the CMB itself, contamination to the BB spectrum by polarized galactic foreground emission needs to be quantified. To improve its ability to characterize polarized foregrounds, Spider will have a second flight in 2018-2019 which will add a 285 GHz frequency channel. In this work, we explore a component separation technique involving Planck HFI data. A power spectrum estimator used to produce bandpower estimates from maps is also discussed. Ph.D. 2019-12-19 00:00:00